Upconversion rare Earths nanomaterials applied to photodynamic therapy and bioimaging - Rezende, Thaís K. L.; Barbosa, Helliomar P.; dos Santos, Luiz F.; de O. Lima, Karmel; Alves de Matos, Patrícia; Tsubone, Tayana M.; Gonçalves, Rogéria R.; Ferrari, Jefferson L. (Frontiers in Chemistry, 2022)
Light-based therapies and diagnoses including photodynamic therapy (PDT) have been used in many fields of medicine, including the treatment of non-oncological diseases and many types of cancer. PDT require a light source and a light-sensitive compound, called photosensitizer (PS), to detect and destroy cancer cells. After absorption of the photon, PS molecule gets excited from its singlet ground state to a higher electronically excited state which, among several photophysical processes, can emit light (fluorescence) and/or generate reactive oxygen species (ROS). Moreover, the biological responses are activated only in specific areas of the tissue that have been submitted to exposure to light. The success of the PDT depends on many parameters, such as deep light penetration on tissue, higher PS uptake by undesired cells as well as its photophysical and photochemical characteristics. One of the challenges of PDT is the depth of penetration of light into biological tissues. Because photon absorption and scattering occur simultaneously, these processes depend directly on the light wavelength. Using PS that absorbs photons on “optical transparency windows” of biological tissues promises deeper penetration and less attenuation during the irradiation process. The traditional PS normally is excited by a higher energy photon (UV-Vis light) which has become the Achilles’ heel in photodiagnosis and phototreatment of deep-seated tumors below the skin. Thus, the need to have an effective upconverter sensitizer agent is the property in which it absorbs light in the near-infrared (NIR) region and emits in the visible and NIR spectral regions. The red emission can contribute to the therapy and the green and NIR emission to obtain the image, for example. The absorption of NIR light by the material is very interesting because it allows greater penetration depth for in vivo bioimaging and can efficiently suppress autofluorescence and light scattering. Consequently, the penetration of NIR radiation is greater, activating the biophotoluminescent material within the cell. Thus, materials containing Rare Earth (RE) elements have a great advantage for these applications due to their attractive optical and physicochemical properties, such as several possibilities of excitation wavelengths – from UV to NIR, strong photoluminescence emissions, relatively long luminescence decay lifetimes (µs to ms), and high sensitivity and easy preparation. In resume, the relentless search for new systems continues. The contribution and understanding of the mechanisms of the various physicochemical properties presented by this system is critical to finding a suitable system for cancer treatment via PDT.